2012
DOI: 10.7763/ijbbb.2012.v2.91
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing and Spectroscopic Properties of Natural Dyes on Poly (Lactic Acid) and Poly (Ethylene Terephthalate) Fabrics

Abstract: The current research studied the dyeing properties and spectroscopic characteristics of natural dyes on PLA and PET fabrics. The natural dyes used were the dyes extracted from turmeric and cassumunar powder and the commercial dyes viz. Natural Orange and Natural Red Brown. The water solubility and partition of the dyes in octanol and water (logP) were studied. It was found that the dyes with poor water solubility that were the turmeric and cassumunar dyes exhibited a high degree of exhaustion and visual color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Recently several efforts were made to study fluorescence property of synthetic and natural fibers dyed with natural dyes and encouraging results were observed [14,26]. In view of these facts current study was undertaken to (i) characterize the fluorescence property of woolen yarn dyed with Acacia nilotica natural fluorescent dye, (ii) investigate the durability of fluorescence finish, (iii) investigate the fluorescence fading rate of dyed fiber under influence of UV radiations, (iv) investigate the adsorption behavior of dye on wool fiber, and (v) assess the effects of metal salts on fluorescence property of dyed fiber.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently several efforts were made to study fluorescence property of synthetic and natural fibers dyed with natural dyes and encouraging results were observed [14,26]. In view of these facts current study was undertaken to (i) characterize the fluorescence property of woolen yarn dyed with Acacia nilotica natural fluorescent dye, (ii) investigate the durability of fluorescence finish, (iii) investigate the fluorescence fading rate of dyed fiber under influence of UV radiations, (iv) investigate the adsorption behavior of dye on wool fiber, and (v) assess the effects of metal salts on fluorescence property of dyed fiber.…”
Section: Introductionmentioning
confidence: 92%
“…Several new applications of fluorescent dyes have emerged particularly exploiting their light emmision properties and mainly include non-destructive flaw detection [5], tunable dye lasers [6][7][8][9], liquid crystal displays [10,11], solar collectors [12], and electroluminicent displays [13]. With the discovery of synthetic fibers in the middle of 19th century, use of fluorescent dyes generated much scientific attention for use in textile coloration [14], coatings [15], and plastics. Among those fluorescent dyes napthalimide and coumarin derivatives have been recommended for coloration of synthetic fibers [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The study was accomplished on exhaust dyeing of knitted fabrics made from PET and PLA fibers (Sriumaoum et al, 2012). PLA is reported to give higher shade depth with curcumin as compared to PET at the same dye concentration (Sriumaroum et al, 2011).…”
Section: Dyeing Pla With Natural Dyesmentioning
confidence: 99%
“…At this time three dyeing studies were carried out by changing temperature from 70 0 C to 110 0 C shown in figure 2, 3 and 4. After dyeing the dye bath was cooled down and reduction clearing was carried out [4].…”
Section: Dyeingmentioning
confidence: 99%
“…corn, sugar and starch. Fermentation of the materials yields lactic acid which is then used for PLA polymerization [1].…”
Section: Introductionmentioning
confidence: 99%